Combined Extradural and Intradural Pterional Transzygomatic Approach to Large Sphenoid Wing Meningiomas. Operative Technique and Surgical Results - González-Darder, José M. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives Describe a unique and safe surgical procedure for the microsurgical management of large sphenoid wing meningiomas (SWMs) aimed to a radical resection of these tumors.Design A prospective series of 26 cases with SWMs larger than 3 cm in one of its main diameter is presented. All patients were studied following the same clinical and imaging procedures. The surgical approach was through a pterional transzygomatic craniotomy. The surgical procedure has the following steps: 1. Extradural tumor devascularization and resection of the hyperostotic and/or infiltrated bone and then intradurally; 2. Intradural tumor debunking; 3. Microdissection of vascular branches and perforators from the capsule; 4. Identification of the optic and oculomotor nerves and internal carotid artery; 5. Tumor capsule dissection and resection; 6. Dural resection or cauterization; 7. Dural and bone reconstruction and closing.Results All lesions were completely removed. Most complications were transient. The most relevant complication was a large middle cerebral artery infarct with permanent hemiplegia despite a decompressive craniotomy.Conclusion Large SWMs can be considered as a single pathology regarding the surgical approach and intraoperative microsurgical procedure strategies. The pterional transzygomatic approach allows an extradural devascularization of the tumor and an extensive bone resection that facilitates the intradural stage of tumor resection. The proposed approach allows a wide and radical resection of the duramater and bone that increases the Simpson grade. However, surgery does not control other biological or molecular prognostic factors involved in tumor recurrence.
Keywords: sphenoid wing meningioma; pterional craniotomy; transzygomatic craniotomy; meningioma recurrence